2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8461315
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Approach for Eeg-Based Emotion Recognition Using Brain Connectivity and its Spatial Information

Abstract: Emotion recognition based on electroencephalography (EEG) has received attention as a way to implement human-centric services. However, there is still much room for improvement, particularly in terms of the recognition accuracy. In this paper, we propose a novel deep learning approach using convolutional neural networks (CNNs) for EEG-based emotion recognition. In particular, we employ brain connectivity features that have not been used with deep learning models in previous studies, which can account for synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 17 publications
1
63
0
Order By: Relevance
“…Moon et al [15] presented a CNN-based emotion recognition model for EEG signals. A major difference of their approach is its brain connectivity features, used to account for synchronous activation of many different brain regions.…”
Section: Cnn-based Modelsmentioning
confidence: 99%
“…Moon et al [15] presented a CNN-based emotion recognition model for EEG signals. A major difference of their approach is its brain connectivity features, used to account for synchronous activation of many different brain regions.…”
Section: Cnn-based Modelsmentioning
confidence: 99%
“…With the recent explosion of deep learning techniques, there are studies to apply deep learning to brain signal analysis. It was shown that several deep neural networks such as deep belief networks, stacked denoising autoencoders, and convolutional neural networks can extract effective application-driven features for EEG signals in spatial and spectral domains [10] [11][12] [13]. Deep learning models on graph signals, especially graph convolutional neural networks (GCNN) [5] [6] have been considered as competitive approaches for analyzing MEG [14] and fMRI [15] signals.…”
Section: Related Workmentioning
confidence: 99%
“…For example, ICU monitoring tools are able to perform live diagnosis based on some ECG recordings. Unfortunately, the efficiency of this tool remains a problem (Kim, 2018) In the literature, a number of studies have been placed to find automatic diagnostic tools for ECG signals (Acharya et al, 2017a;Kiranyaz et al, 2016;Moon et al, 2018). (Acharya et al, 2018a(Acharya et al, , 2017a From the scientists' point of view, the heart is very completed and different and new types of arrhythmia can affect the heart.…”
Section: Application Of Cnn For Ecg Analysismentioning
confidence: 99%